Prevalence, Management of Placenta Previa, and Pregnancy Outcomes: An Update Systematic Review - Juliana, Mutia; Nurlianto, Yahya (International Medical Journal Corp. Ltd, 2024)
Background:Placenta previa increases the risk of postpartum hemorrhage, leading to maternal deaths. Risk factors include advanced maternal age, multiparity, smoking, and cesarean section. Traditional treatments include hemostatic balloons, surgical sutures, and uterine artery embolization. Methods: Using PRISMA 2020 criteria, this systematic review focused on full-text English literature published between 2014 and 2024. Without a DOI, editorials and review pieces published in the same publication as the submission were rejected. The literature was compiled using various internet databases, including PubMed, ScienceDirect, and SagePub. Result: Following a thorough three-level screening process, seven publications were identified as being closely related to our current comprehensive study. Following that, the entire content was thoroughly reviewed, and these articles were subjected to extra scrutiny. Conclusion: The Society of Obstetrics and Gynecology recommends interventional treatment for placenta previa patients at high risk of hemorrhage, including balloon occlusion, to reduce bleeding, shorten operation time, and reduce postoperative complications.